The effectiveness of an online training program in a nursing unit: extraction of blood cultures - Zaragoza-García, Ignacio; Pérez-García, Santiago; Orellana-Miguel, María de los Ángeles; Posé-Becerra, Clotilde; Goñi-Olangua, María Andión (Revista da Escola de Enfermagem da USP, 2019)
Objective: To assess the effectiveness of an online training platform for procedures among nurses in an internal medicine unit to reduce the number of contaminated blood cultures. Method: This was a quasi-experimental pre-post intervention parallel group study. The sample consisted of internal medicine nurses in a tertiary hospital who participated in an online training program about blood culture extraction technique. Knowledge about the technique was measured pre- and post-intervention. Additionally, the study compared the number of blood cultures taken 6 months before and 3 months after the intervention. Results: Forty-eight nurses participated. Pre-intervention knowledge was homogeneous among both groups, improving significantly after the online training program (p=0.0001). The blood cultures taken prior to the training showed contamination levels above international standards; post-intervention, contamination levels fell by up to 3% in the intervention group. Conclusion: The educational intervention using the digital platform increased knowledge about the procedure and its application in clinical practice.